2009
DOI: 10.1080/01942630902784746
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Experiences of Adolescents with Cerebral Palsy

Abstract: The purpose of this study was to describe how youth with cerebral palsy experience mobility in their daily lives using a phenomenological approach. The participants were 10 youth with cerebral palsy, 17 to 20 years of age, selected using purposeful sampling with maximum variation strategies. A total of 14 interviews were completed. Transcripts were analyzed for key concepts and themes. Credibility was established through triangulation of researchers and member checking. Participants viewed mobility as importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 26 publications
1
68
1
1
Order By: Relevance
“…The participants made individual choices in mobility based on environmental and personal factors, such as the family culture, personal habits, personality and associated impairments. These findings have similarities with a study by Palisano et al [30]. Their results suggest that mobility choices are based on the importance of being self-sufficient, and on environmental factors, safety and efficiency in mobility.…”
Section: Discussionsupporting
confidence: 89%
“…The participants made individual choices in mobility based on environmental and personal factors, such as the family culture, personal habits, personality and associated impairments. These findings have similarities with a study by Palisano et al [30]. Their results suggest that mobility choices are based on the importance of being self-sufficient, and on environmental factors, safety and efficiency in mobility.…”
Section: Discussionsupporting
confidence: 89%
“…This is associated with mobility, with young people reporting that it is essential for self-sufficiency and making choices (Palisano et al, 2009). Some interviewees in the current study thought that the standing frame limited their mobility and independence, because they had to rely on others for help whilst in the standing frame.…”
Section: Size-lack Of Spacementioning
confidence: 99%
“…The descriptive literature supports a social model, studying the person in the context of environment, versus a medical model, which focuses on the context of disability (Colver et al, 2012;Palisano et al, 2009;van Wely, Balemans, Becher, & Dallmeijer, 2014). Study findings reported that environmental variables (accessibility, attitude, adaptations) were found to be as effective for improving self-help skills and mobility as conventional therapeutic interventions focused on changing the child (Colver et al, 2012).…”
Section: Methods To Engage Adolescents With Cerebral Palsy In Physicamentioning
confidence: 82%
“…Changes in mobility can be seen over time and may be due to the child's growth and changes in environment as they move from home to school to work (Tieman et al, 2004). There is a lack of knowledge of how interventions affect PA across the lifespan (Turk, 2009) and longitudinal research is needed to track progress into adulthood (Palisano et al, 2009).…”
Section: Numbers and Types Of Studiesmentioning
confidence: 99%